Sustainable Development in Uttarakhand through Tourism: Challenges and Strategies for Sustainable Tourism Development in Uttarakhand (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The emphasis of this paper is on sustainable tourism growth in Uttarakhand. Uttarakhand is a state in the North Himalayan zone of India and has become a hot spot for tourism because of its magnificently varied farmland, strong biodiversity of ample religious tourism potential and an abundance of cultural heritage. The tourism industry is one of the largest and fastest expanding business sectors in the world community with major positive and negative impacts on the climate, culture, society and the state. Tourism is regarded as the biggest and fastest expanding sector in the world. The key aims of the analysis are the development of tourism tours in order to recognize problems and formulate an effective strategy for sustainable tourism in Uttarakhand.